Meningkatan keaktifan dan hasil belajar IPS melalui model jigsaw pada materi atmosfer dan hidorsfer - Agus Suprasetyo (Universitas Negeri Malang, 2019)
Seventy-five percent of Social Studies learning outcomes in atmospheric material and hydrosphere students at Pesanggrahan 2 Batu One Roof Junior High School, scored below the average KKM. That encourages teachers to implement improvements in social studies learning in the classroom. Improved learning designed into classroom action research activities. The learning method used in learning classroom action is a type of jigsaw cooperative learning. Data collection uses observation techniques using a collection of observation sheets. How in the first cycle, through a type of jigsaw cooperative learning model, student learning outcomes in solving social studies questions for junior high school class VII can improved. Students who completed the study in the first cycle of classroom action research, 30%, with an average value of 48, while in the first cycle, 78% of students completed the study with an average value of 71. In cycle II, students were active in studying social studies material on atmospheric material, and the VII grade junior high school hydrosphere was successful. Cycle I classroom action research-active students only 46%. While after completing the second cycle of action the percentage of activity reached 82%. The results of this study prove the role of giving more to students in learning considering the improvement in learning outcomes.DOI: 10.17977/um022v4i22019p096